2000
DOI: 10.1054/bjoc.2000.1174
|View full text |Cite
|
Sign up to set email alerts
|

True

Abstract: Currently the only tumour marker to have a well-defined and validated role in the management of ovarian cancer is CA125. Changes in the level of CA125 can be used as a reliable indication of response or progression according to various criteria, but it does not yet have a clear place in diagnosis or prognosis. Its value as part of a screening tool and during routine follow-up remain the subject of ongoing trials. Other markers remain experimental and do not have a well-defined contribution to make at present. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…In this study, no objective responses were obtained but 10 women (17%) had stable disease on scan for at least 12 weeks. Using Rustin’s criteria [13, 14], the investigators observed a partial CA 125 response in 8% of patients. The tumor marker fell <50% and then remained stable in another 14 patients (23%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, no objective responses were obtained but 10 women (17%) had stable disease on scan for at least 12 weeks. Using Rustin’s criteria [13, 14], the investigators observed a partial CA 125 response in 8% of patients. The tumor marker fell <50% and then remained stable in another 14 patients (23%).…”
Section: Discussionmentioning
confidence: 99%
“…A 75% response occurred if there was a fall in the value of CA 125 by 75% over three samples. In each case, the final sample had to be analysed at least 28 days from the preceding sample [13, 14]. Stable value was defined as a <50% rise in the CA 125 level for at least three months.…”
Section: Methodsmentioning
confidence: 99%
“…However, CA125 is the only currently used diagnostic biomarker for ovarian CCC. Furthermore, CA125 is also elevated in patients with endometriosis (EMS), from which CCC is thought to arise [9, 10]. Although it is very important to monitor the transformation from EMS into CCC, there is currently no biomarker that can efficiently distinguish between these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…7 Changes in the level of CA-125 and other laboratory workup can be used as a reliable indicator of response or progression, but these do not, yet, have a clear place in diagnosis or prognosis. 8,9 Ultrasound (US) is the first-line imaging investigation in the detection and characterization of ovarian tumours, but on the other hand, it is an operator-dependent technique, less panoramic than MRI and shows less distinction of solid soft-tissue components. 10 MRI can distinguish several types of tissue and fluid from their signal intensity (SI) patterns.…”
Section: Introductionmentioning
confidence: 99%